Training model for extended career athletes: A narrative review - Caparros, T. (Sports Health: A Multidisciplinary Approach, 2025)
Context: Today`s elite and professional sports tend to feature older, more seasoned athletes, who have longer sporting careers. As advancing age can potentially limit peak performance, balancing training load is necessary to maintain an optimal state of performance and extend their sports career.